Exogenous acquisition of Pseudomonas aeruginosa in intensive care units: a prospective multi-centre study (DYNAPYO study). Issue 1 (January 2020) - Coppry, M.; Leroyer, C.; Saly, M.; Venier, A-G.; Slekovec, C.; Bertrand, X.; Parer, S.; Alfandari, S.; Cambau, E.; Megarbane, B.; Lawrence, C.; Clair, B.; et al.
Summary: Background: Pseudomonas aeruginosa remains one of the most common nosocomial pathogens in intensive care units (ICUs). Although exogenous acquisition has been widely documented in outbreaks, its importance is unclear in non-epidemic situations. Aim: To elucidate the role of exogenous origin of P. aeruginosa in ICU patients. Methods: A chronological analysis of the acquisition of P. aeruginosa was performed using samples collected in 2009 in the DYNAPYO cohort study, during which patients and tap water were screened weekly. Molecular relatedness of P. aeruginosa isolates was investigated by pulsed-field gel electrophoresis. Exogenous acquisition was defined as identification of a P. aeruginosa pulsotype previously isolated from another patient or tap water in the ICU. Findings: The DYNAPYO cohort included 1808 patients (10, 402 samples) and 233 water taps (4946 samples). Typing of 1515 isolates from 373 patients and 375 isolates from 81 tap water samples identified 296 pulsotypes. Analysis showed exogenous acquisition in 170 (45.6%) of 373 patients. The pulsotype identified had previously been isolated from another patient and from a tap water sample for 86 and 29 patients, respectively. The results differed according to the ICU. Conclusion: Exogenous acquisition of P. aeruginosa could be prevented in half of patients. The overall findings of this survey support the need for studies on routes of transmission and risk assessment approach to better define how to control exogenous acquisition in ICUs.